SHU’UBATU KITABATI AL-JUMALI AL-‘ARABIYYATI LADA THULLABI MA’HADI MAWARIDISSALAM BATANGKAIS DELI SERDANG SUMATRA AL-SYIMALIYYAH - Baiq Laili Rahmawati; Ali Fuddin Nasution; Uril Bahruddin (El-Tsaqafah : Jurnal Jurusan PBA, 2022)
Abstract This research is a research oriented to the analysis of difficulties in writing Arabic sentences in third grade students of Tsnawiyah Mawaridussalam, Batangkais, North Sumatra. The purpose of this study is to find out what difficulties are experienced by students, what factors cause these difficulties, and how they affect students. This study use descriptive qualitative research methods, while the data collection techniques use unstructured interviews and data analysis using the Miles and Huberman model, namely data reduction, presentation, and verification. The results of this study indicate that students still have difficulty in distinguishing letters that have a similar appearance and makharijul letters are similar. The influencing factors are divided into internal factors in the form of interest, motivation, and knowledge of students towards the mufradat and qaidah of Arabic writing and external factors in the form of environment, teachers, and infrastructure. These difficulties have an impact on students' academic achievement. This study shows that the difficulties and factors as well as the impact on the difficulty of writing Arabic for each person are different, but cannot be separated from the things that have been mentioned in the study. Keywords: Difficulty, Writing Skills, Students, Learning Arabic ?????? ??? ????? ????? ?? ??? ???? ?????? ???????? ?? ????? ????? ??????? ??? ???? ???? ?????? ???????? ????? ??????? ??????????? ?????? ????????. ????? ?? ??? ??????? ?? ????? ???????? ???? ??????? ??????? ???????? ???? ???? ??? ????????? ???? ???? ??? ??????. ?????? ??? ??????? ??? ????? ?????? ???????? ????? ?????? ?????? ??? ???????? ????????? ??? ??????? ?????? ???????? ???????? ????? ????? ????????? ?? ????? ???????? ?????? ???????. ???? ????? ??? ??????? ??? ?? ?????? ?? ????? ??????? ????? ?? ????? ?????? ???? ??? ???? ????? ??? ????? ??????. ????? ??????? ??????? ??? ????? ?????? ?? ??? ?????? ?????? ?????? ?????? ???? ???????? ???????? ?? ??????? ??????? ???????? ???????? ?? ??? ?????? ????????? ??????? ???????. ??? ???????? ??? ????? ??? ??????? ??????? ??????. ???? ??? ??????? ?? ???????? ???????? ?????? ??? ????? ????? ????? ??????? ??? ??? ??????? ???? ?? ???? ????? ?? ??????? ???? ?? ????? ?? ???????. ??????? ?????????: ?????? ????? ???????? ??????? ????? ????? ???????.